CuBr2-catalyzed enantioselective routes to highly functionalized and naturally occurring allenes1. Issue 6 (15th June 2015) - Tang, Xinjun; Huang, Xin; Cao, Tao; Han, Yulin; Jiang, Xingguo; Lin, Weilong; Tang, Yang; Zhang, Jiasheng; Yu, Qiong; Fu, Chunling; Ma, Shengming
<x xml:space="preserve">Abstract</x> CuBr2-catalyzed highly enantioselective synthesis of functionalized 1, 3-disubstituted allenes including three natural ones from readily available terminal alkynes, aldehydes, and (S)-α, α-diphenylprolinol has been demonstrated.